Evolution of the locomotory system in eels (Teleostei: Elopomorpha). Issue 1 (December 2016) - Pfaff, Cathrin; Zorzin, Roberto; Kriwet, Jürgen
Abstract Background Living anguilliform eels represent a distinct clade of elongated teleostean fishes inhabiting a wide range of habitats. Locomotion of these fishes is highly influenced by the elongated body shape, the anatomy of the vertebral column, and the corresponding soft tissues represented by the musculotendinous system. Up to now, the evolution of axial elongation in eels has been inferred from living taxa only, whereas the reconstruction of evolutionary patterns and functional ecology in extinct eels still is scarce. Rare but excellently preserved fossil eels from the Late Cretaceous and Cenozoic were investigated here to gain a better understanding of locomotory system evolution in anguilliforms and, consequently, their habitat occupations in deep time. Results The number of vertebrae in correlation with the body length separates extinct and extant anguilliforms. Even if the phylogenetic signal cannot entirely be excluded, the analyses performed here reveal a continuous shortening of the vertebral column with a simultaneous increase in vertebral numbers in conjunction with short lateral tendons throughout the order. These anatomical changes contradict previous hypotheses based on extant eels solely. Conclusions The body curvatures of extant anguilliforms are highly flexible and can be clearly distinguished from extinct species. Anatomical changes of the vertebral column and musculotendinous system through time and between extinct and extant anguilliforms correlate with changes of the body plan and swimming performance and reveal significant shifts in habitat adaptation and thus behaviour. Evolutionary changes in the skeletal system of eels established here also imply that environmental shifts were triggered by abiotic rather than biotic factors (e.g., K/P boundary mass extinction event).